The impact of local protests on political elite communication: evidence from Fridays for Future in Germany - Lennart Schürmann (Journal of Elections, Public Opinion and Parties, 2024)
The Climate Strike Movement (or Fridays for Future) is one of the most prominent transnational protest movements nowadays. In this paper, I examine the reactions of politicians to this movement to answer the research question: To what extent have German Members of Parliament (MPs) been responsive to local environmentalist street protests by focusing their attention on the Climate Strike Movement and Environmental Policy? To this end, I apply dictionary-based quantitative text-analytical tools to study German MPs' political communication through 292,949 Facebook posts and 43,644 parliamentary debates between September 2017 and February 2020. Focussing on the effect of the first global climate strike in March 2019 and leveraging varying protest frequencies between the electoral districts, I show that MPs are responsive to protest events in their districts. More local street protest events in an electoral district led to more attention to the Climate Strike Movement and Environmental Policies by political repres
https://osf.io/b5u6z/
Keywords: 330